2016
DOI: 10.1589/jpts.28.246
|View full text |Cite
|
Sign up to set email alerts
|

Changes in joint space width during Kaltenborn traction according to traction grade in healthy adults

Abstract: [Purpose] The aim of this study was to analyze the joint space width of the humeral head and glenoid fossa during traction under 2 grade conditions (grade 2/grade 3). [Subjects and Methods] The subjects were 20 healthy male adults who had not experienced any shoulder injury. Three radiographs were obtained with the subjects in the supine position (resting, grades 2 and 3). The glenohumeral joint space was examined on radiography. Joint space width was measured by a radiologist at the points described by Peters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…These results align with existing literature, where studies (16,10) have demonstrated the effectiveness of exercises, mobilizations, and specifically MET in reducing pain in patients with nonspecific LBP. Additionally, findings on the efficacy of KEOMT in reducing pain in conditions like Frozen Shoulder further corroborate our results (17). The decrease in pain is hypothesized to be a result of neurophysiological effects, potentially altering pain perception through manual contact and applied movement (18).…”
Section: Discussionsupporting
confidence: 85%
“…These results align with existing literature, where studies (16,10) have demonstrated the effectiveness of exercises, mobilizations, and specifically MET in reducing pain in patients with nonspecific LBP. Additionally, findings on the efficacy of KEOMT in reducing pain in conditions like Frozen Shoulder further corroborate our results (17). The decrease in pain is hypothesized to be a result of neurophysiological effects, potentially altering pain perception through manual contact and applied movement (18).…”
Section: Discussionsupporting
confidence: 85%
“…Although the subjects were instructed to remain relaxed, we cannot rule out that some defensive contractions may have occurred during the application of the technique. It has been described that there is a reactive contraction in the contractile tissues as a reactive force to any load applied to the glenohumeral joint [ 35 ]. This defensive contraction may have minimised the sideways movement, so the results may have been lower than expected.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have already evaluated the reliability of detecting degrees of movement, showing good to excellent intra-observer reliability [ 39 , 43 , 44 , 45 , 46 , 47 ]. Ultrasound measurements are reliable for assessing inferior gliding of the humeral head [ 22 , 27 , 28 , 35 ]. The present study observed excellent intra-observer reliability (ICC greater than 0.992), exceeding SEM in all applied force magnitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La tracción cosiste en la distracción de una superficie articular con el propósito de generar una tensión. Kaltenborn establece tres grados de tracción, el grado 1 en el que la fuerza es mínima pero suficiente para eliminar la compresión en la superficie articular, el grado 2 en el que se procura eliminar la holgura articular tensando los tejidos periarticulares y el grado 3 en el que se aplica una fuerza mayor consiguiendo separar los tejidos blandos que se encuentra alrededor de articulación (6). Los síntomas, generalmente dolor y limitación funcional son evidentes tanto en su fase aguda como crónica; más frecuente en pacientes mayores de 40 años (7).…”
Section: Introductionunclassified